(untitled) (Bangladesh Journal of Urology, 2026)
Introduction: Penile fracture is a rare andrological emergency. Disruption of tunica albuginea of penis and tear of corpus cavernosum occur during sexual intercourse. Majority of the patients come to the emergency department immediately after the trauma and should be corrected early surgically. Objective: To evaluate outcomes of repairing in patients who had sexual intercourse-induced fracture penis and underwent early surgical repair. Materials and Methods: We retrospectively evaluated records of 97 patients who underwent early surgical repair due to sexual induced fracture penis between January 2012-July 2024 at Cumilla Medical College Hospital and private clinics. Age was 20-65 years, mean 45 years. Patients preoperative, peroperative and postoperative data were analyzed meticulously. Patients clinical features, penile trauma characteristics, pre-trauma and postoperative International Index of Erectile Function, Erectile Function Domain Scores (IIEF-ED), and operation note were evaluated. Follow up period was 6 months to 7 years. Results: Total 97 patients who underwent early repair due to sexual intercourse induced fracture penis were investigated. 85 (87.62%) patients had unilateral corpus cavernosum rupture and 9 (9.27%) had bilateral corpus cavernosum rupture and 3(3.09%) patients had bilateral corpus cavernosum rupture with concomitant urethral rupture. 91 patients (93.42%) showed successful repair. Postoperative erectile dysfunction was observed in 4 patients (4.12%). Penile curvature developed postoperatively in 2 patients (2.06%). Whereas none of the patients developed voiding dysfunction. Conclusion: Early repair with degloving approach is effective method in sexual intercourse-induced penile fracture for satisfactory outcome. Early repair also helps postoperative erectile success in young patients with isolated unilateral fractures. Bangladesh J. Urol. 2025; 28(2): 67-70